EKSPLORASI JEJAK DAN KERAGAMAN AGAMA DI DUNIA - Laila, Nurul Hidayah, Irfan Musadat (JIPI (Jurnal Ilmiah Pendidikan Islam), 2024)
This article explores the history and diversity of world religions, focusing on some of the major religions such as Hinduism, Islam, Christianity, Buddhism, Sikhism, Zoroastrianism, Sinti, Bahá'í, Taoism, and Shinto. The exploration starts from Hinduism which has three important aspects: Vedic religion, Brahmanism, and Shaktism. Next, Islam, which originated in Arabia and teaches faith in Allah and the Prophet Muhammad. Then, Christianity from Israel which believes in Jesus Christ. This article also describes Buddhism from India, which worships Buddha as a teacher and deity. The Sikh religion from India that worships Guru Nanak Dev is also included in this article. Zoroastrianism from Iran, Sinti from Germany, Bahá'í from Iran, Taoism from China, and Shinto from Japan are also the focus of this study. This article provides a detailed overview of the various religions of the world and how their beliefs and practices affect human life in various cultural, social and political aspects. It provides a better understanding of the diversity of religions in the world and the complexity of the relationship between religious beliefs and personal identity in multicultural societies.